2022
DOI: 10.4314/udslj.v17i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Technology Usage and Public Procurement Performance in Tanzania

Abstract: Given a number of challenges procurement in the public sector faces also in line with the current trend of globalization and innovation, organizations are trying much to improve their procurement practices through technological applications. However, still there are contradictory results on the role of technology usage on the performance of procurement. This study was aimed at investigating the public procurement performance in Tanzania by examining the roles played by technology usage and regulatory pressure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…E-procurement contributes to accountability, transparency and anti-corruption efforts by offering centralised platforms, standardised processes, real-time monitoring, automated evaluations, reliable audit trails and data-driven analysis. Therefore, leveraging e-procurement system promotes integrity, reduces human bias and improves the overall efficiency and fairness in pharmaceutical procurement processes (Maran and Lowe, 2022; Tinali, 2022; Israel, 2023; Aduwo et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-procurement contributes to accountability, transparency and anti-corruption efforts by offering centralised platforms, standardised processes, real-time monitoring, automated evaluations, reliable audit trails and data-driven analysis. Therefore, leveraging e-procurement system promotes integrity, reduces human bias and improves the overall efficiency and fairness in pharmaceutical procurement processes (Maran and Lowe, 2022; Tinali, 2022; Israel, 2023; Aduwo et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these audit trails provide a complete historical record of procurement processes, thus enabling effective monitoring, evaluation and accountability. By automating specific steps in pharmaceutical procurement system, e-procurement system reduces the potential for human interference and bias (Pentrakan et al, 2022;Tinali, 2022). This, in turn, helps in mitigating the risk of corruption stemming from personal connections or undue influence.…”
Section: 23mentioning
confidence: 99%
“…Hence, the results in Table 4 suggest that integrated health commodities procurement system mediates the relationship between the predictor variable (responsiveness) and the outcome variable (health service delivery). These findings are supported by the fact that responsiveness is critical for supporting the adoption of integrated health commodities procurement system (Svidronova and Mikus, 2015;Tinali, 2022), and integrated health commodities procurement system is essential for health service delivery (Srivastava and Singh, 2021;Israel et al, 2019;Cholette et al, 2019). Responsiveness may thus improve health service delivery through integrated health commodities procurement system.…”
Section: Structural Model and Testing Of Hypothesesmentioning
confidence: 93%
“…This is because integrated health commodities procurement system fosters efficiency, accountability and transparency, enhances timely delivery and minimises errors and costs in the course of procurement and delivery of health services (Svidronova and Mikus, 2015). These findings are supported by Tinali (2022) and Cholette et al (2019) who established that public health facilities can achieve better health service delivery in terms of cost-effective and accessibility by centralising and integrating the procurement and distribution of health commodities. Besides, this study emphasises the integration of health commodities procurement systems as a pathway through which government health facilities can improve health service delivery.…”
Section: Structural Model and Testing Of Hypothesesmentioning
confidence: 94%
“…Yet, compliance with procurement laws and regulations among procuring entities remains unimpressive (Changalima, 2016;Matto et al, 2021;Tinali, 2022). For instance, it was found that 42 local government authorities (LGAs) did not comply with regulation 55(2), 163(4), and 185(1) of the public procurement regulations by making procurements without obtaining the required tender board approval [National Audit Office of Tanzania (NAOT, 2021)].…”
Section: Introductionmentioning
confidence: 99%